Increased IgG4 expression within tertiary lymphoid structures of esophageal cancer and implications for prognosis - Su, Chanjuan; Chen, Shuqi; He, Xuqing; Ma, Changchun; Huang, Wei; Zhu, Chunyan; Wang, Hui; Gu, Jiang (Frontiers in Immunology, 2025)
BackgroundTertiary lymphoid structures (TLS) have been observed in various tumors, including esophageal squamous cell carcinoma (ESCC), where they function as active centers of humoral immunity within the tumor microenvironment, facilitating the production of distinct immunoglobulin (Ig) subtypes with diverse effects. This study aimed to investigate the expression of TLS-associated Ig in ESCC and its prognostic significance.MethodsA retrospective analysis was conducted on 109 ESCC cases. TLS presence was evaluated using immunohistochemistry, and the expression of Ig-positive cells was assessed. Additionally, gene expression profiles related to TLS were analyzed with gene chip data from 274 ESCC cases obtained from the GEO database.ResultsAmong the 109 ESCC cases, 69 (63.3%) exhibited TLS, while 40 (36.7%) did not. Patients with TLS demonstrated significantly better prognoses compared to those without TLS (P < 0.001). ESCC tumor tissues with TLS exhibited higher infiltration of Ig-positive immune cells. Among the variables examined, the differential expression of IgG4 was the most pronounced (P = 0.04). Furthermore, ESCC cases exhibiting TLS with elevated IgG4 expression demonstrated a poorer prognosis compared to those with TLS and reduced IgG4 expression (P = 0.036). The presence of TLS in general and low IgG4 expression in TLS were associated with improved survivals in patients who underwent post-surgery chemotherapy (p < 0.001 and p = 0.001, respectively). Analysis of the GEO dataset indicated that predominant IgG4 expression within TLS was associated with a reduced number of activated CD8+ T cells and an increased presence of CD4+ T helper cells and dendritic cells. The expression of TLS in ESCC was linked to a more favorable prognosis, whereas TLS with increased IgG4 expression correlated with a less favorable prognosis.ConclusionsThe differential expression of immunoglobulins within TLS can modulate its function within the tumor microenvironment. In addition to the number of TLSs themselves, the immune heterogeneity present within TLS maybe a critical factor in individualized assessment of tumor immunotherapy.